Advances in applied mechanics. - Aref, Hassan, 1950-; Giessen, E. van der (Academic, 2011)
The Advances in Applied Mechanics book series draws together recent significant advances in various topics in applied mechanics. Published since 1948, Advances in Applied Mechanics aims to provide authoritative review articles on topics in the mechanical sciences, primarily of interest to scientists and engineers working in the various branches of mechanics, but also of interest to the many who use the results of investigations in mechanics in various application areas such as aerospace, chemical, civil, environmental, mechanical and nuclear engineering. .Covers all fields of the mechanical sciences .Highlights classical and modern areas of mechanics that are ready for review .Provides comprehensive coverage of the field in question.